Neglected Fractures of the Lateral Humeral Condyle in Children; Which Treatment for Which Condition? - Giovanni Trisolino; Diego Antonioli; Giovanni Gallone; Stefano Stallone; Paola Zarantonello; Piergiuseppe Tanzi; Eleonora Olivotto; Luca Stilli; Giovanni Luigi Di Gennaro; Stefano Stilli (MDPI AG, 2021)
Background: Neglected fractures of the lateral humeral condyle (LHC) are misdiagnosed or insufficiently treated fractures, presenting later than 3 weeks after injury. The management of neglected LHC fractures in children remains controversial. Methods: Twenty-seven children were included in this retrospective study. Charts and medical records were investigated for demographics, time interval between injury and treatment, and type of treatment. Baseline radiographs were assessed for fracture grading and displacement. Final radiographs were investigated for bone healing, avascular necrosis, elbow deformities and growth disturbances. Complications were classified by the Clavien-Dindo-Sink (CDS) system. Outcomes were assessed according to the Dhillon Score (DhiS) and Mayo Elbow Performance Score (MEPS). Results: The mean time from injury to presentation was 27 months. Treatments included nonoperative management (6 patients), "in-situ" fixation (7 patients), open reduction and internal fixation (11 patients) and corrective osteotomy (3 patients). The mean follow-up was 7 years (range: 2-16). Overall, we observed complications in 16 patients (59%); six complications were considered major (22%) and occurred in Weiss Grade 3 fractures, with lateral displacement ≥5 mm. At the latest follow-up, pain and functional scores improved in 23 of 27 patients (85%). Mean MEPS increased from an average of 62 points preoperatively to 98 points postoperatively, while mean DhiS improved on average from 5 to 8 points. CDS score and time interval between injury and treatment were independent predictors of MEPS and DhiS. Conclusion: Our study describes outcomes from a cohort of children undergoing different treatments for neglected LHC fractures. Prolonged time interval between injury and treatment and perioperative major complications negatively impacted the treatment outcomes. Our findings strengthen the requirement for widely agreed guidelines of surgical management in neglected LHC fractures.